Concept of Ideology: Evolution Tracks - S. A. Sakharova (Дискурс)
Introduction. The modern understanding of ideology is often reduced to defining it as a false consciousness limited to the socio-political context. However, ideology as a constant is integral to the formation of subjective understanding, where mythology, philosophy, religion and science play a key role. In order to critically reflect on the concept of ideology, it is necessary to analyse the route of its development with the works of Destudes de Tracy,  S. Žižek, K. Marx, P. Slotterdijk, Z. Freud and J. Lacan.Methodology and sources. The study is based on a historical-problematic approach and an interpretive-analytical method to analyse the conceptualisation of ideological concepts through original and critical sources.Results and discussion. The French philosopher Destude de Tracy, being a bright representative of the Enlightenment, in his work "Foundations of Ideology" developed an epistemological project of the science of ideas, where he conceptualised the notion of ideology and traced the process of formation of judgement, reflecting the positive nature of the existence of external objects only partially touching upon language as a system of signs and hidden mental processes. Modern philosophy in the person of S. Žižek, who continues the idea of studying ideology as a worldview, vision of being and subjective place, introducing psychoanalytical ideas of the Freud-Lakan school, as well as Marxist ideological concepts, moves away from the positive dimension of the concept of ideology to a negative and dialectical one, asserts the impossibility of separating ideology from non-ideology, and defines ideology itself as a component of language, as an anthropological constant, without which the existence of the subject is unthinkable.Conclusion. The application of the dialectical approach to the epistemological project of idea formation, together with psychoanalytical theories of dreams, phantasm, unconsciousness, as well as Marxist approaches to the concept of ideology as illusory consciousness and the concept of commodity fetishism, allows us to reveal new complex inter-relationships between the form and content of the ideological message.